The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11136-014-0888-0
|View full text |Cite
|
Sign up to set email alerts
|

Gaps between patients’ reported current and preferred abilities versus clinicians’ emphases during an episode of care: Any agreement?

Abstract: The MAM-CAT facilitated direct comparison of patients' current-preferred gaps at initiation and discharge with clinicians' emphases during episodes of care. While interventions were perceived as effective, collaboration between patients and clinicians using gap data could increase alignment between patient priorities and clinician emphases, potentially resulting in improved patient engagement and rehabilitative outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The first part of the study assessed differences in patient priorities as revealed by the movement dimensions showing the largest gaps on the MAM-CAT (Fig. 4.4) and clinician emphases as revealed by the health records of assessments and interventions during the episode of physical therapy [12]. Although both the MAM-CAT and physical therapy notes indicated that patients progressed, comparison showed poor or slight agreement on the movement dimensions to prioritize (Fig.…”
Section: Person-centered Disability As a Measure Of Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The first part of the study assessed differences in patient priorities as revealed by the movement dimensions showing the largest gaps on the MAM-CAT (Fig. 4.4) and clinician emphases as revealed by the health records of assessments and interventions during the episode of physical therapy [12]. Although both the MAM-CAT and physical therapy notes indicated that patients progressed, comparison showed poor or slight agreement on the movement dimensions to prioritize (Fig.…”
Section: Person-centered Disability As a Measure Of Effectivenessmentioning
confidence: 99%
“…Several essential areas continue to evolve with the integration of PROMs in EHR technology: accessibility for rapid point-of-care data collection and visualization as well as remote administration of PROMs, and data integration into routine clinical management. The objectives of data integration into routine management is for the clinician to be alerted to changes and patient priorities, and clinicians and patients to review person-centered data together so that the measures play a part in shared decision-making [12].…”
Section: Accessibility and Conveniencementioning
confidence: 99%
“…Allen et al [11] document a gap between patient' and clinicians' assessment of rehabilitation progress. Using a computer-adapted patient-reported outcome, they examined current-versus-ideal gap in movement ability from the perspective of the patient, and compared this gap to physical therapists' clinic notes.…”
Section: Why Patient Engagement Is Importantmentioning
confidence: 99%